Faktor-faktor resiko kejadian asfiksia pada bayi baru lahir - Eka Riana; Purnomo Suryantoro; Umu Hani Edi Nawangsih (Universitas Aisyiyah Yogyakarta, 2016)
Abstract :This study aims to identify risk factors asphyxia in newbornsat PKU Muhammadiyah Hospital in Bantul 2014. The type of researchthat is used is the analytic survey design with Case Control Study. Totalsample of 167 cases and 167 controls. Data analysis was performedusing univariate, bivariate with chi-square test and multivariate logisticregression analysis. Multivariate analysis there are four factors relatedto the type of birth asphyxia is not normal (OR = 2.304; 95% CI =1.402 to 3.787; p-value = 0.001), premature rupture of membranes(OR = 2.040; 95% CI = 1,019- 4.083; p-value = 0.044), anemia(OR = 1.426; 95% CI = 1.182 to 1.720; p-value = 0.000) and spacingof pregnancy 2 years (OR = 2.458; 95% CI = 1.060 to 5.698; pvalue = 0.036). Type of abnormal labor, premature rupture ofmembranes, anemia and pregnancy spacing 2 years is a risk factorasphyxia in newborns.Keywords: asphyxia, neonatal risk factors